THE HETTANGIAN SHALLOW WATER CARBONATES AFTER THE TRIASSIC/JURASSIC BIOCALCIFICATION CRISIS: THE ALBENZA FORMATION IN THE WESTERN SOUTHERN ALPS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
This study investigates the stratigraphic and sedimentologic setting of an early Hettangian carbonate platform in the Lombardy Basin, taking into account the Triassic-Jurassic (Tr-J) post-crisis evolution and the geodynamic setting related to the beginning of the Early Jurassic rifting. The historical name of this platform ("Conchodon Dolomite"), not adequate for the absence of Conchodon and for the mainly calcareous lithology, has been replaced with Albenza Formation. The depositional model of this carbonate platform unit is coherent with a leeward Great Bahama Bank-type environment, without any reefs facing deep water environments. The unusual abundance of ooids and marine cements, in the basal progradational ramp-type margins, reflects temporal variation in the saturation state of seawater after the Tr-J crisis, possibly due to marine calcified cyanobacteria blossom. The absence of biotically induced margins related to the (biocalcification) Tr-J crisis and the concomitant tectonic fragmentation, with different subsidence rates of the Tethyan passive margin, conditioned the drowning and the eastward retrogradation of the Albenza platform.
Keywords: Carbonate platform facies; Early Hettangian; Lombardy Basin; Calcified cyanobacteria